Runaways : best friends forever - Rowell, Rainbow; Vaughan, Brian K.; Alphona, Adrian (Vaughan, Brian K., 2018)
When the Runaways eliminate the Pride from Los Angeles, it leaves a vacuum of power in the city's underworld, and soon Nico, Karolina, Gert, Chase, and Molly are on the run again to uncover the truth behind their parents' past before it catches up to them.